Skolēnu spēju attīstība gleznošanā 2. klasē - Cimare, Iveta (Latvijas Universitāte, 2008)
Diplomdarbu autore ir izstrādājusi par tēmu - „Skolēnu spēju attīstība gleznošanā 2. klasē.” Mērķis ir izpētīt skolēnu spēju –iztēles un fantāzijas nosacījumus un iespējas glezniecības apguvē 2. klasē. Tika sastādīta un realizēta mācību programma vizuālajā mākslā, spēju attīstīšanā - balstoties uz Hibneres un citām teorētiskajām nostādnēm. Skolēnu spēju pārbaudei autore izmantoja pētījuma metodes- skolēnu radošo darbību analīzi un datu apstrādi un skolēnu pašvērtējuma anketu un datu apstrādi. Diplomdarba struktūra - ievads; 3 nodaļas; nobeigums - secinājumi un ieteikumi; 42 izmantoto avotu un literatūras saraksts; 3 pielikumi.

The author of the diploma work has worked out the theme “the development of student creative abilities in painting in from 2”. The aim is to develop the student’ abilities – “their capability, imaginations, fantasy in studying painting in class 2”. The teaching programme was compiled and realized in visual arts and students’ abilities were developed by using Hibnere’s and other well known theoretical viewpoints. Jo examine the students’ abilities the author has used research methods – the analysis of students creative activity according to the presented data and self – esteem questionnaires. The structure of the diploma work consists of Introduction, 3 chapters, conclusion, proposals, recommendations, the list of the used literature, three appendixes.
Development of pupils’ painting skills in Grade 2
Keywords: Pedagoģija